Relationship between LBW and the incidence of stunting in toddlers aged 1-3 years at the Minasa Upa Health Center, Rappocini district - Athiyah Ulya Arif; Purnamaniswaty Yunus; Syatirah Jalaluddin (UNUSA Press, 2022)
Background: Stunting is a long-term effect of chronic malnutrition that causes disturbances in a person's physical growth which is characterized by a decrease in growth speed. Unbalanced food intake, LBW (Low Birth Weight Babies), and a history of the disease are the three main factors that play a role in the incidence of stunting. The purpose of this study was to determine the relationship between a history of LBW and the incidence of stunting for toddlers aged 1-3 years at the Minasa Upa Health Center in 2019. Methods: This research is a quantitative study with an observational approach, using a cross-sectional method. Samples were taken by the purposive sampling method. The number of samples is 134 children with the mother of the child as the respondent. The data were processed and analyzed using the Chi-square p<0.05 test in the SPSS program. Results: The results showed that there was a significant relationship between a history of low birth weight and stunting (p = 0.000) with an OR value of 18.8 which means that children aged 1-3 years who have a history of low birth weight have a risk of 18.8 times experiencing stunting. Interventions that focus on maternal and child health care are needed to reduce the risk of babies with low birth weight and stunting, as well as raise awareness of mothers about the importance of good nutrition for mothers and their children. Conclusion: Based on this study, it can be concluded that there is a relationship between a history of LBW and the incidence of stunting in toddlers 1-3 years at the Minasa Upa Public Health Centre.